HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SABIT PADA ATLET PENCAK SILAT UNIVERSITAS PGRI PALEMBANG - Al Azis Hardi (STKIP ROKANIA, 2017)
This study aims to determine the relationship of the leg muscle power with the velocity sabit kick martial arts athletes PGRI University of Palembang. Themethod used is quantitative method using saturated sampling technique. The study population was martial arts athlete PGRI University of Palembang of 20people. The data analysis technique used is the product moment correlation and t test. The results showed that there was a significant relationship between leg muscle power with a sabit kick velocity of ≥ rtabel rhitung = 0.622 = 0.468. Hypothesis testing results showed that t = 3.399 ≥ table = 1.734. Then the leg muscle power has a significant relationship to the velocity of the sabit kick martial arts athletes PGRI Palembang University of 38.68%, and the remaining 61.32% influenced by other factors.